PERCEPTIONS DES PROBLÈMES ENVIRONNEMENTAUX DANS LA COMMUNE DE YAMOUSSOUKRO EN CÔTE D’IVOIRE - Wandan Eboua Narcisse; Ngoran Ngoran Julien; Kouadio Kouakou Bob; Beda K. Julien-Gomez (European Scientific Journal, ESJ, 2014)
The aim of this study was to investigate the perception of population as to their comprehension of environmental management concerns in the city of Yamoussoukro. To do this, a survey completed by interviews and focus group was conducted. The results indicated that the perception of environmental problems was the same regardless of education level. The main environmental preoccupations mentioned by population were: air pollution (57%), poor urbanization (47.6%) , bush fires (56.3%), wastewater discharge (39%), and soil erosion (35%). Forty four percent of the population recognized being misinformed on environmental issues and seems to have more confidence in the state compare to local administration. The results indicated that 78 % of the population claims to make efforts to protect the environment but field observations proved otherwise. To assist in the preservation of the urban environment, 65 % of the population was willing to pay a little more taxes. But they desire by 93%, that the level of awareness of the population regarding environmental issues be raised and that heavy fines for offenders be set. Regarding solid waste, 42.9 % know where they are stored and only 20% know that their taxes are used to pay for collection of this waste. Populations (70, 3 %) say that they eliminate plastic bags by throwing them in the trash but in reality, they discard them by throwing anywhere once used. This study has showed that the policy of environmental planning at the municipality level should focus on integrated management, population implication and education.